2019
DOI: 10.3906/zoo-1806-26
|View full text |Cite
|
Sign up to set email alerts
|

New location, food composition, and parasitic fauna of the invasive fish Pseudorasbora parva (Temminck & Schlegel, 1846) (Cyprinidae) in Poland

Abstract: The species' rapid dispersal has been facilitated by growing international aquaculture logistics; however, the fish owes it to itself that invading water bodies outside its endemic range may be so successful, as its life history traits allow adaptation and survival in new environments. These mainly include a strong reproductive capability, parental care, and a wide spectrum of tolerated food (Pollux et al., 2006). The dynamic spreading process of the invader has been under scrutiny of a number of authors, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous studies showed that the accidental introduction of non-native fish produced a sharp, rapid expansion into the ecological niche occupied by native fish, leading to a sharp decline in native fish resources and their eventual extinction [19,20]. Furthermore, the time of Japanese smelt reproduction (January-April) [47] precedes that of the icefish [18] and other species like the sharpbelly [51] and the topmouth gudgeon, an omnivorous fish [52][53][54] that feeds on zooplankton and benthic animals. The result led to food shortages during the early stages of the icefish [55,56], thus causing its decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the accidental introduction of non-native fish produced a sharp, rapid expansion into the ecological niche occupied by native fish, leading to a sharp decline in native fish resources and their eventual extinction [19,20]. Furthermore, the time of Japanese smelt reproduction (January-April) [47] precedes that of the icefish [18] and other species like the sharpbelly [51] and the topmouth gudgeon, an omnivorous fish [52][53][54] that feeds on zooplankton and benthic animals. The result led to food shortages during the early stages of the icefish [55,56], thus causing its decline.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that the CPUE of topmouth gudgeon decreased significantly after the invasion of Japanese smelt, as well as the changes in CPUE of Japanese smelt and topmouth gudgeon CPUE were significantly negatively correlated. Topmouth gudgeon is an omnivorous fish [52][53][54], which feeds mainly on zooplankton and benthic animals in Lake Erhai [61]. The reproduction of the Japanese smelt population in Lake Erhai occurs mainly from January to April [47], which is earlier than that of the topmouth gudgeon [62].…”
Section: Discussionmentioning
confidence: 99%
“…In the inland waters of Turkey, this order is represented by 278 species according to Çiçek, Sungur, and Fricke (2020). Ecology of parasites of the order Cypriniformes has been the center of an increasing attention for two decades (Dorovskikh & Stepanov, 2009;Soylu, Uzmanoğlu, Çolak, & Soylu, 2017;Gabagambi & Skorping, 2018;Czerniejewski, Rybczyk, Linowska, & Sobecka, 2019).…”
Section: Introductionmentioning
confidence: 99%